A Morphological Analysis Of Derivational Process (Suffix) -Ment And -Ness Used In Oxford English Dictionary Published 2003 - Rahmayani, Nurul; , Drs. Sigit Haryanto, M. Hum; , Siti Fatimah S. Pd. M. Hum (2013)
This research aims at knowing the character of base in derivational process (suffix) -ment and -ness, and explaining the function of derivational process (suffix) -ment and -ness used in Oxford English Dictionary. The type of this research is descriptive qualitative. The technique of collecting data is documentation. The steps are reading dictionary, classifying and analyzing the data, taking note, and browsing to the internet. To answer those problems, this research employs morphological analysis. The objectives are identifying and analyzing the new derived words whether or not they have changed based on syntactical category. The result of the research shows that derivational process (suffix) by -ment are in 30% words of the dictionary, and derivational process (suffix) by -ness are in 70% words of the dictionary. The function of derivational process (suffix) -ment changes the grammatical categories from the verb into noun and function of derivational process (suffix) -ness changes the grammatical categories from the adjectives into noun.